Pengaruh Implementasi Pendekatan Kontruktivisme Model Needham Terhadap Hasil Belajar Ditinjau dari Kemampuan Komunikasi Matematis - Purnomo, Agus Purnomo; Hasyim, Maylita (Universitas PGRI Madiun, 2019)
AbstractThis study aims to analyze whether: (1) the influence of the approach of contracting the needham model to the mathematics learning outcomes; (2) the influence of students' mathematical communication ability on the mathematics learning outcomes; and (3) the influence of the implementation of the needham's approach to the learning outcomes in terms of communication skills mathematical. This research uses a quantitative approach with experimental design and causal comparative research. Sampling technique with cluster sampling. Data collection techniques are mathematical communication ability test and learning outcomes test. Hypothesis testing using anava technique of two cell lines is not equal to 5% significance level. Prior to hypothesis test, prerequisite test was done by equilibrium test with t test of two independent samples, normality test with kolmogorov-smirnov test and homogeneity test with f test. The result of anava technique of two cell lines is not equal shows that: (1) there is influence of the approach of contracting of Needham model to the result of learning mathematics: (2) there is influence of mathematical communication ability to the learning result of mathematics: (3) no influence of the approach of contracting of Needham model to the result of mathematics learning in terms of mathematical communication.